Spatio-temporal analysis of dog ecology and rabies epidemiology at a wildlife interface in the Lowveld Region of South Africa - Knobel, Darryn Leslie (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.